Tracking the roots of cellulase hyperproduction by the fungus Trichoderma reesei using massively parallel DNA sequencing - Le Crom, Stéphane; Schackwitz, Wendy; Pennacchio, Len; Magnuson, Jon K; Culley, David E; Collett, James R; Martin, Joel; Druzhinina, Irina S; Mathis, Hugues; Monot, Frédéric; Seiboth, Bernhard; Cherry, Barbara; et al. (Proceedings of the National Academy of Sciences - PNAS, 2009)
Trichoderma reesei (teleomorph Hypocrea jecorina) is the main industrial source of cellulases and hemicellulases harnessed for the hydrolysis of biomass to simple sugars, which can then be converted to biofuels such as ethanol and other chemicals. The highly productive strains in use today were generated by classical mutagenesis. To learn how cellulase production was improved by these techniques, we performed massively parallel sequencing to identify mutations in the genomes of two hyperproducing strains (NG14, and its direct improved descendant, RUT C30). We detected a surprisingly high number of mutagenic events: 223 single nucleotides variants, 15 small deletions or insertions, and 18 larger deletions, leading to the loss of more than 100 kb of genomic DNA. From these events, we report previously undocumented non-synonymous mutations in 43 genes that are mainly involved in nuclear transport, mRNA stability, transcription, secretion/vacuolar targeting, and metabolism. This homogeneity of functional categories suggests that multiple changes are necessary to improve cellulase production and not simply a few clear-cut mutagenic events. Phenotype microarrays show that some of these mutations result in strong changes in the carbon assimilation pattern of the two mutants with respect to the wild-type strain QM6a. Our analysis provides genome-wide insights into the changes induced by classical mutagenesis in a filamentous fungus and suggests areas for the generation of enhanced T. reesei strains for industrial applications such as biofuel production.